Formulation of micron-scale carrier particles of nanoparticulate drug : effects of nanoparticle size, chemical nature and concentration. - Kok, Hui Hua. (2009)
Pulmonary delivery of the nanoparticles to the lungs serves as an attractive route due to the high solute permeability and large surface area for absorption. The nanoparticles are able to escape the phagocytic clearance mechanism in the lungs, but their small sizes often results in the particles being exhaled. Hence large hollow nanoparticles aggregates (LHNPA) are required. The desirable properties for the morphology of these LHNPA are obtained through the variations and investigations of three parameters namely the nanoparticle sizes, concentrations and chemical natures (silica and PMMA). The nanoparticles are then spray-dried and characterized under the Scanning Electron Microscope (SEM). Spray-drying low concentration levels such as 0.3-0.8% of nanoparticles are able to give spherical and hollow aggregates. In addition, it was found that large nanoparticle sizes are able to form thinner aggregates shell. However as the sizes of these nanoparticles reach micron-scale; they are unable to form LHNPA due to the similarities in sizes of the spray droplets. From the investigation of silica and PMMA, it was found that silica had a better morphology as compared to PMMA. The aggregate strength study on the silica particles also show that non-hollow and non-spherical particles are difficult to break.